Porous polyvinyl alcohol/biochar hydrogel induced high yield solar steam generation and sustainable desalination. Issue 3 (June 2022) - Li, Jing; Yan, Liangguo; Li, Xuguang; Song, Wen; Li, Yanfei
Abstract: Solar vapor generation is one of effective techniques in alleviating freshwater shortages. However, targeted gaps of high-efficient solar harvesting and fast evaporation rate still existed. In this work, the polyvinyl alcohol/biochar hydrogels (PBHs) with different water/PVA ratio were fabricated as the effective solar-driven vapor generator. The openly porous structure facilitated the intense capillary effect and water transport to PBH surface. Moreover, the proportion of intermediate water changed with the water/PVA ratio and further reduced the evaporation enthalpy. The solar absorber on the biochar interface confined the convective heat and reduced the heat loss. These properties induced the generation rate of PBH-10 achieving 1.89 kg m −2 h −1 with the solar-to-vapor convection efficiency of 85.2% under 1 sun irradiation. The thermal conduction well fitted to the heat distribution in the evaporation system according to COMSOL simulation. The rate of water vaporization by PBH-10 also maintained excellent performance in the salt rejection and wastewater purification containing different pollutants. It is anticipated that the PBH evaporator provided new possibilities in the clean water collection, desalination, and wastewater purification under natural sunlight. Graphical Abstract: ga1 Highlights: PVA skeleton availed water activation and reduced vaporization enthalpy. Openly porous accelerated water pumping and absorber confined heat in the interface. The evaporation rate reach 1.89 kg m −2 h −1 with 85.2% energy efficiency under 1 sun. PHB-10 had excellent capability of desalination and wastewater purification.